Industrial policy in export-oriented economies lessons from the experiences of Japan, South Korea and Taiwan - Patalinghug, Epictetus E. (1992)
The paper describes the experiences of Japan, South Korea and Taiwan in their successful export-oriented development. A comparison of industrial policies in these three economies indicates that their governments actively and consciously intervene to influence specific firms and industries. However, most export incentives were administered uniformly across all industries. At the same time, incentives were granted based on output performance within a limited duration in an environment that encouraged policy reforms and market orientation. Some of the important lessons to be learned from the experiences of these three export-oriented economies are the involvement of the private sector in the promotion of exports and the establishment of a system of export targets.
Keywords: Foreign trade regulation; Industrial policy; International trade